Bactericidal Potential of Extract Citrus Hystrix D.C.Leaf Powder on Staphylococcus aureus and Salmonella typhi - Elfira Maulidah; Anny Thuraidah; Leka Lutpiatina (Politeknik Kementerian Kesehatan Banjarmasin, 2021)
Infectious diseases can be caused by bacteria such as Staphylococcus aureus and Salmonella typhi. Treatment of infectious diseases can use antibiotics. However, antibiotics can cause side effects on users. Kuit Lime leaf (Citrus hystrix D.C.) contains secondary metabolites such as alkaloids, steroids, triterpenoids, tannins, and flavonoids used as antibacterial. This study aimed to determine the bactericidal potential of the kuit lime leaf extract powder on Staphylococcus aureus and Salmonella typhi. The type of research used is the experiment, and the research design used is the Posttest Only Control Group Design. The antibacterial activity test used was the liquid dilution of MIC and MBC. The results showed the MIC of Staphylococcus aureus and Salmonella typhi was 180 mg/mL and 120 mg/mL, while the MBC results against Staphylococcus aureus and Salmonella typhi are 190 mg/mL and 130 mg/mL. Data analysis in this research conducted descriptively. Based on descriptive analysis, it concluded that the bactericidal potential of the powdered extract of kuit lime against Staphylococcus aureus is at a concentration of 190 mg/mL and Salmonella typhi at a concentration of 130 mg/mL.